Influenza and other respiratory viruses: standardizing disease severity in surveillance and clinical trials. Issue 6 (3rd June 2017) - Rath, Barbara; Conrad, Tim; Myles, Puja; Alchikh, Maren; Ma, Xiaolin; Hoppe, Christian; Tief, Franziska; Chen, Xi; Obermeier, Patrick; Kisler, Bron; Schweiger, Brunhilde
ABSTRACT: Introduction : Influenza-Like Illness is a leading cause of hospitalization in children. Disease burden due to influenza and other respiratory viral infections is reported on a population level, but clinical scores measuring individual changes in disease severity are urgently needed. Areas covered : We present a composite clinical score allowing individual patient data analyses of disease severity based on systematic literature review and WHO-criteria for uncomplicated and complicated disease. The 22-item ViVI Disease Severity Score showed a normal distribution in a pediatric cohort of 6073 children aged 0–18 years (mean age 3.13; S.D. 3.89; range: 0 to 18.79). Expert commentary : The ViVI Score was correlated with risk of antibiotic use as well as need for hospitalization and intensive care. The ViVI Score was used to track children with influenza, respiratory syncytial virus, human metapneumovirus, human rhinovirus, and adenovirus infections and is fully compliant with regulatory data standards. The ViVI Disease Severity Score mobile application allows physicians to measure disease severity at the point-of care thereby taking clinical trials to the next level.